(untitled) (Al-Academy, 2018)
Magical realism potential bulwark plastic art and literature، and won great fame and Research cash innumerable، and like other currents of literary found his outlet in the art of cinema، quoted cinema of literature magical realism and influenced his concepts، and Arab cinema، it was necessary to have a vulnerability to stream، either Tools employing magical realism، unintentionally since the early beginnings dating back to the time of World Wars I and II، or in deliberate more mature in the twenty-first century، due to the emergence of film-makers more aware and culture، and more friction global currents. But this raises a number of problems that need to be addressed from the maker of the film، because of the difference between the Arab culture and religious and social values ​​Arabic between them and Western civilization in general Of these problems posed by this research humble، problematic eating taboo subjects or that give rise to allergies such as religion، and problematic tournament collective and bypass the idea of ​​the hero sole، and finally problematic time and breadth of the time of the story in the film world by carving toward the stream magical realism، and how to handle the maker Arab action for this formats